A case report on congenital methemoglobulinemia-neonatal cyanosis - Mathews, Aswathy; Prazad, Amal (International Journal of Research in Medical Sciences, 2025)
Methemoglobin (MetHb) is a form of hemoglobin where iron is in an oxidized ferric state, impairing its oxygen-binding capacity. This condition can be hereditary or acquired, leading to methemoglobinemia when MetHb levels exceed 3%. Hereditary methemoglobinemia, although rare, presents with hypoxia and cyanosis. This case report discusses a 1-month 7-day-old female diagnosed with congenital methemoglobinemia caused by NADH-cytochrome b5 reductase deficiency, characterized by persistent cyanosis unresponsive to oxygen therapy. The patient presented with fever, loose stools, vomiting, and respiratory distress. Initial examination revealed significant findings including pallor, hyperpigmentation of the skin, tachycardia, tachypnea, and respiratory failure. Diagnosis involved ABG with co-oximetry, revealing high MetHb levels and severe metabolic acidosis. Management included methylene blue administration, packed red blood cells (PRBC) transfusion, and supportive care. Despite initial treatment challenges, the patient showed clinical improvement with normalization of methemoglobin levels. This report emphasizes the need for accurate diagnosis and careful management of congenital methemoglobinemia to prevent complications.